1990
DOI: 10.1111/j.1744-7976.1990.tb03525.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Price Distortions Caused by Canadian Wheat Board Initial Payment Policy

Abstract: Limited Dependent variable regression techniques are used to measure price distortitons caused by initial payments as price floors. The result indicate that the degree of uncertainty producers have regarding the price floor is the critical issue in the level of price distortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Conceptually Bardsley and Cashin correctly identify the government guarantee as a type of put option; however, the Black-Scholes option pricing model will overprice the option when price averaging is part of the model. Clark and Fleming (1990) analyze price distortions in CWB initial payment price policy using a Tobit procedure that specifically recognizes the truncation introduced in prices with the initial payment price guarantee. This indirectly acknowledges that the guarantee acts as a put.…”
Section: Conceptual Financial Models In Poolingmentioning
confidence: 99%
“…Conceptually Bardsley and Cashin correctly identify the government guarantee as a type of put option; however, the Black-Scholes option pricing model will overprice the option when price averaging is part of the model. Clark and Fleming (1990) analyze price distortions in CWB initial payment price policy using a Tobit procedure that specifically recognizes the truncation introduced in prices with the initial payment price guarantee. This indirectly acknowledges that the guarantee acts as a put.…”
Section: Conceptual Financial Models In Poolingmentioning
confidence: 99%
“…5 is not equal to the price rational producers would predict. Clark and Fleming (1990) considered this problem in detail and concluded that the truncation of price due to initial payments as being floors is small. Therefore, this problem is ignored in this paper.…”
Section: Notesmentioning
confidence: 99%
“…However, as Nerlove (1956) noted, farmers react not only to last year's price, but also to the price they expected that depends on the last year's price with a limited extent. And Clark and Fleming (1990) and Yang et al (2015) argued that price support policy issued by the government that sets the price floors for crops would alter farmers' price expectations. But in the literature on price policy in China, the main method of incorporating the price policy is to construct dummy variables for estimation (Zhang et al, 2020), which might be rough as it ignores the impact of floor prices on farmers' price expectations.…”
Section: Introductionmentioning
confidence: 99%